Determination of caesium-137 in water samples using modified carbon microfibers - Silliková, Veronika; Jakubčinová, Jana; Horník, Miroslav; Gomola, Igor; Dulanská, Silvia (Journal of radioanalytical and nuclear chemistry, 2022)
In this paper, the possibility of caesium sorption on microfibres produced by the Slovak Academy of Sciences was investigated. Sorption capacity limit of sorbent was increased by chemical modification. The binding of Cs to the surface of potassium copper ferrocyanide modified carbon microfibers was demonstrated by SEM–EDX analysis. Statistical comparison of the models showed that the Freundlich isothermal model was more suitable for describing sorption processes. The influence of desorption, pH value, competing ions and water volume were also tested. According to the results, this method seems to be suitable for large-scale caesium separation from contaminated waters.